Scientometric analysis of the scientific productivity of "Odovtos-International Journal of Dental Sciences" : collaborative networks, trends and dynamicity = Análisis cienciométrico de la productividad científica de "Odovtos-Revista Internacional de Ciencias Dentales" : Redes colaborativas, tendencias y dinámica - Espinoza Carhuancho, Fran
This study aim to analyze the scientific productivity of the journal "Odovtos-International Journal of Dental Sciences" during the period from 2019 to 2023. Manuscripts were selected from the Scopus database using the search criterion `SRCTITLE ("Odovtos-International Journal of Dental Sciences") AND PUBYEAR > 2019 AND PUBYEAR < 2024`. During the evaluated period, 164 manuscripts were identified in the journal. Of these, 36 articles, 14 reviews, 7 editorials, and 7 letters to the editor were evaluated. The selected manuscripts were analyzed in terms of their content, authors, institutions, countries of origin, keywords provided by the authors, and citations received. Amaury De Jesús Pozos-Guillen, from the Universidad Autónoma de San Luis Potosí in Mexico, had the highest academic production with a total of 10 publications. Adrián Gómez-Fernández, from the University of Costa Rica, showed a high Field-Weighted Citation Impact (Field-Weighted Citation Impact) with a value of 0.45, having received 43 citations in total. The University of Costa Rica led in terms of academic production with 44 publications. The Universidad Científica del Sur in Peru produced 15 publications. Despite having only 5 publications, the Universidad Arturo Prat in Chile achieved a high citation impact weighted by field of 0.86. The results of the analysis provided valuable insight into scholarly production and collaboration among authors in the journal. The findings of this study may be useful for researchers, journal editors, and policy makers to better understand the dynamics and trends in the field of dental sciences.